2022
DOI: 10.3390/agronomy12102518
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Drought Stress on Water Use Efficiency and Grain Productivity of Rice and Utilization of Genotypic Variability to Combat Climate Change

Abstract: Rice is an important cereal and drought stress is a critical abiotic stress that negatively influences the performance and productivity of rice crop, particularly under a changing climate scenario. The objectives of this study were to evaluate the impacts of drought stress on grain productivity and water use efficiency of rice cultivars and to assess the genotypic variability among the tested cultivars. Two irrigation treatments including a control and drought stress were applied to the experiments during 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Otherwise, antioxidant enzymes and proline content compared to non-stressed conditions. These results were in harmony with previously published studies that confirmed the negative impact of drought stress on the numerous physiological and agronomic characteristics of rice (Panda et al, 2021;Hussain et al, 2022;Moukoumbi et al, 2023).…”
Section: Discussionsupporting
confidence: 93%
“…Otherwise, antioxidant enzymes and proline content compared to non-stressed conditions. These results were in harmony with previously published studies that confirmed the negative impact of drought stress on the numerous physiological and agronomic characteristics of rice (Panda et al, 2021;Hussain et al, 2022;Moukoumbi et al, 2023).…”
Section: Discussionsupporting
confidence: 93%
“…The water cycle has been substantially altered by climate change, which has also increased the severity of droughts [93]. Hence, efficient water use in agricultural systems is a basic concern in the current scenario.…”
Section: Smart Irrigation Techniquesmentioning
confidence: 99%
“…Many studies have shown that water use efficiency (WUE) is an important functional index related to plant growth and productivity, and it is used to determine crop optimal water management [49]. In the present study, the WUE differed depending on the plant organ (stem, leaf, grain) from one water treatment to another.…”
Section: Sorghum Water Use Efficiency and Ability To Recover From Ear...mentioning
confidence: 74%